Efficacy of adjunctive autologous serum in the comprehensive treatment of bacterial corneal ulcers in patients with diabetic mellitus - O. V. Zavoloka; P. A. Bezditko (Journal of Ophthalmology, 2020)
Background: The presence of diabetic keratopathy associated with diabetic corneal neuropathy should be taken into account in the management of corneal inflammation in patients with diabetes mellitus.